Сучасні засоби підвищення рівня безпеки броньованих легкових автомобілів - Вайда, Т. С.; Vaida, T. S. (Право і безпека. - 2013. - № 2 (49). - С. 112-119, 2013)
Розглянуто сучасні методи технічного вирішення проблеми захисту VIP-персон та забезпечення безпеки перевезення цінних вантажів як одного з пріоритетних напрямків діяльності спеціальних підрозділів правоохоронної сфери. Критично оцінено можливості сучасного заводського і післязаводського бронювання спецтранспорту як ефективної умови їх надійного захисту в екстремальних умовах можливого нападу, проаналізовано основні напрямки підвищення їх безпеки: 1) зміцнення кузова; 2) застосування куленепробивних стекол; 3) використання коліс із захистом від проколів (пробоїв); 4) підсилення підвіски; 5) застосування додаткового обладнання. Аргументовано доведено переваги застосування інноваційних технічних засобів для безпеки перевезення VIP-пасажирів та збереження цінних вантажів у процесі їх транспортування.

The ways of technical decision of problem of defense of VIP-people and providing of safety of transportation of valuable loads as one of priority directions of activity of the special subdivisions of series of establishments − governmental service of guard, bank and financial and credit organizations, operative groups of accompaniment of militia, cars of secret service of internal troops of MIA etc are considered in the article. Possibilities of the modern plant and post-plant reserving of special transport as an effective condition of their reliable defence in the extreme terms of possible attack are critically appraised, basic directions of increase of their safety are analysed: 1) work-hardening of basket; 2) application of bulletproof glasses; 3) the use of wheels with protecting from punctures (hasps); 4) strengthening of suspension bracket; 5) application of additional equipment. The advantages of application of innovative technical facilities for safety of transported VIPpassengers (safety of valuable loads) at their transporting are proved: 1) technology of «sandwich» made of a thin armour, ceramics and polymers; light armour-laminate of Armormax 3,9 of synfils − for hardening of basket of car; 2) bullet-proof multi-layered bent glasses with an internal polycarbonate layer − for a safety review; 3) selfhermetic overlays; tires with the increased sideframes; tires with the special systems of support (wheels of Мichelin РАХ type with internal replacing a tire insertions (metallic, plastic); multicamerate tires; models of wheels with the independent pumping of air − for maintenance of safe driving; 4) additional equipment: specially protected accumulator and computer block of engine, systems of the controlled from distance start of engine, serve of clean air, automatic extinguishing of fire; increased suspension bracket, protecting of petrol tank from an explosion and flowing of fuel − for providing of vital functions of people and machine. Recommendations to the subjects of guard are offered: 1) to take into account at the equipment of the reserved cars existent modern developments of hardwares for their defence; 2) to use the special equipment for increasing safety of transporting of VIP-persons (valuable load) and warning of possible attack.

Рассмотрены методы технического решения проблемы защиты VIP-персон и обеспечения безопасности перевозки ценных грузов как одного из приоритетных направлений деятельности специальных подразделений правоохранительной сферы. Критически оценены возможности современного заводского и послезаводского бронирования спецтранспорта как эффективного условия их надежной защиты в экстремальных условиях возможного нападения, проанализированы основные направления повышения их безопасности: 1) упрочнение кузова; 2) применение пуленепробиваемых стекол; 3) использование колес с защитой от проколов (пробоев); 4) усиление подвески; 5) применение дополнительного оборудования. Аргументированно доказаны преимущества применения инновационных технических средств для безопасности перевозимых VIP-пассажиров (сохранности ценных грузов) при их транспортировке.
Modern facilities for increasing the strength of security of the reserved passenger cars
Современные средства повышения уровня безопасности бронированных легковых автомобилей
Keywords: спеціальні (броньовані) автомобілі; безпека; цінний вантаж; засоби захисту; special (reserved) cars; safety; valuable load; means of protection; специальные (бронированные) автомобили; безопасность; ценный груз; средства защиты